Analisis Faktor Produksi Usahatani Tumpang Sari Tanaman Padi dan Jagung Desa Nagabosar - Zandroto, Febri Damai Hasrat; Sibuea, Faiz Ahmad (Jurnal Ilmiah Pertanian ( JIPERTA), 2025)
The purpose of this study was to analyze production factors on rice and corn crop yields in Nagabosar Village, Simalungun Regency, North Sumatra. The problem is focused on the production factors of intercropping rice and corn. In order to approach this problem, the method used is analysis with the COBB-Douglas production function approach. The main data were collected by surveys from 30 farmers who have implemented the Tumpang sari system in Nagabosar Village, Pematang Silimahuta District, Simalungun Regency, North Sumatra Province. The results showed that land area factors, urea fertilizer, KCL fertilizer had an effect on rice crop production, while seeds, SP36 fertilizer, pesticides and labor did not affect rice crop production in Nagabosar Village. Then in corn plants, land area factors, urea fertilizer and KCL fertilizer had an effect on production, while seed factors, SP36 fertilizer, pesticides and labor had no effect on corn crop production in this village. Based on the results of this study, it is hoped that farmers who intercrop rice and corn will pay more attention to production factors such as land area, seeds and others to increase the production of both crops and increase farmers' income.